The Potential of Plant Diversity in Bukit Barisan Selatan National Park in Support of Achieving National Curriculum Goals - Wisnu Juli Wiono; Nadya Meriza (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2021)
This study aimed to describe the diversity of plants found in Bukit Barisan Selatan National Park. The analysis of plant diversity was carried out by applying the quadratic method. Twenty-five squares were constructed for sampling. The results showed that there were thirty two (32) plant tribes consisting of 256 individuals in the exposed area and 899 individuals in the burial area. Data on plant diversity were then mapped to be correlated with Basic Competence (BC) at each level of the educational unit. Mapping results showed, there are 6 BC at the elementary school level; 5 BC at the junior high school level; and 7 basic competencies at high school level that can be learned by utilizing information on plant diversity of Bukit Barisan Selatan National Park. Based on the results of the analysis, it is known that the existence of plant diversity in Bukit Barisan Selatan National Park has the potential to support the achievement of the objectives of the national curriculum.Penelitian ini bertujuan untuk menggambarkan keanekaragaman tumbuhan yang terdapat di Taman Nasional Bukit Barisan Selatan (TNBBS). Analisis kenakeragaman tumbuhan dilakukan dengan menerapkan metode kuadrat. Dua puluh lima petak berbentuk bujur sangkar dibuat untuk pengambilan sampel. Hasil penelitian menunjukkan bahwa terdapat tiga puluh dua (32) suku tumbuhan yang terdiri atas 256 individu di tempat terdedah dan 899 individu di tempat ternanung. Data tentang keanekaragaman tumbuhan selanjutnya dipetakan untuk dikorelasikan dengan Kompetensi Dasar (KD) di setiap tingkat satuan pendidikan. Hasil pemetaan menunjukkan, terdapat 6 KD di tingkat sekolah dasar (SD); 5 KD di tingkat SMP; dan 7 KD di tingkat SMA yang dapat dibelajarkan dengan memanfaatkan informasi keanekaragaman tumbuhan TNBBS. Berdasarkan hasil analisis diketahui bahwa keberadaan keanekaragaman tumbuhan di TNBBS berpotensi mendukung tercapainya tujuan kurikulum nasional.Kata kunci: keanekaragaman, kurikulum, Taman Nasional Bukit Barisan SelatanDOI: http://dx.doi.org/10.23960/jbt.v9i1.22014